High-throughput peptide-centric local stability assay extends protein-ligand identification to membrane proteins, tissues and bacteria - Li, Kejia; Potel, Clément M.; Becher, Isabelle; Hüttmann, Nico; Garrido-Rodriguez, Martin; Schwarz, Jennifer Jasmin; Burtscher, Mira Lea; Savitski, Mikhail M. (Nature structural & molecular biology, 2026)
Systematic mapping of protein-ligand interactions is essential for understanding biological processes and drug mechanisms. Peptide-centric local stability assay (PELSA) is a powerful tool for detecting these interactions and identifying potential binding sites. However, its original workflow is limited in throughput, sample compatibility and accessible protein targets. Here, we introduce a high-throughput adaptation—HT-PELSA—that increases sample processing efficiency by 100-fold while maintaining high sensitivity and reproducibility. HT-PELSA substantially extends the capabilities of the original method by enabling sensitive protein-ligand profiling in crude cell, tissue and bacterial lysates, allowing the identification of membrane protein targets in diverse biological systems. We demonstrate that HT-PELSA can precisely and accurately determine binding affinities of small molecule inhibitors, sensitively detect direct and allosteric ATP binding sites, and reveal off-target interactions of a marketed kinase inhibitor in heart tissue. By enhancing scalability, reducing costs and enabling system-wide drug screening across a wide range of sample types, HT-PELSA—when combined with next-generation mass spectrometry—may offer a powerful platform poised to accelerate both drug discovery and basic biological research.
Online veröffentlicht: 5. November 2025
Gesehen am 09.02.2026